Microbiomes of Healthy and Bleached Corals During a 2016 Thermal Bleaching Event in the Upper Gulf of Thailand - Kusdianto, Heru; Kullapanich, Chitrasak; Palasuk, Matanee; Jandang, Suppakarn; Pattaragulwanit, Kobchai; Ouazzani, Jamal; Chavanich, Suchana; Viyakarn, Voranop; Somboonna, Naraporn (Frontiers in Marine Science, 2021)
Global warming has caused elevated seawater temperature and coral bleaching, including events on shallow reefs in the upper Gulf of Thailand (uGoT). Previous studies have reported an association between loss of zooxanthellae and coral bleaching. However, studies on the microbial diversity of prokaryotes and eukaryotes (microbiome) as coral holobionts are also important and this information is still limited in the uGoT. To address this shortcoming, this report provided baseline information on the prokaryotic (bacteria and archaea) and eukaryotic microbes of healthy and bleached colonies of four prevalent corals Acropora humilis, Acropora millepora, Platygyra sinensis, and Porites lutea and surrounding seawater and sediments, using 16S and 18S rRNA gene next-generation sequencing. Both prokaryotic and eukaryotic microbes showed isolated community profiles among sample types (corals, sediment, and seawater) (ANOSIM: P < 0.001, R = 0.51 for prokaryotic profiles and P < 0.001, R = 0.985 for eukaryotic microbe profiles). Among coral species, P. sinensis showed the most diverse prokaryotic community compared with the others (ANOSIM: P < 0.001, R = 0.636), and P. lutea showed the most diverse eukaryotic microbes (P = 0.014, R = 0.346). Healthy and bleached corals had some different microbiomes in species and their prevalences. For instance, the significant increase of Alphaproteobacteria in P. sinensis resulted in reduced prokaryotic community evenness and altered potential metabolic profiles (i.e., increased amino acid metabolism and genetic information processing and transcription, but decreased prokaryotic functions in cell motility, signaling, and transduction). For eukaryotic microbes, the loss of the algal Symbiodinium (colloquially known as zooxanthellae) in bleached corals such as P. lutea resulted in increased Chromista and Protista and, hence, clearly distinct eukaryotic microbe (including fungi) communities in healthy vs. bleached colonies of corals. Bleached corals were enriched in bacterial pathogens (e.g., Acinetobacter, Helicobacter, Malassesia, and Aspergillus) and decreased coral-beneficial prokaryotic and eukaryotic microbes (e.g., Rhizobiales and Symbiodinium). Additionally, this study identified microbiome species in bleached P. lutea that might help bleaching recovery (e.g., high abundance of Rhizobiales, Oceanospirillales, Flavobacteriales, and Alteromonadales). Overall, our coral-associated microbiome analyses identified altered diversity patterns of bacteria, archaea, fungi, and eukaryotic microbes between healthy and bleached coral species that are prevalent in the uGoT. This knowledge supports our ongoing efforts to manipulate microbial diversity as a means of reducing the negative impacts of thermal bleaching events in corals inhabiting the uGoT.